Drengestreger - Studier i drenge, mænd og maskulinitet - Sørensen, Anne Scott (Kvinder, Køn & Forskning, 1999)
The article outlines the new international research area, the so-called "Boyhood Studies" and the corresponding Nordic boyhood studies that are seen in interaction with on the one hand the recent men’s Studies and masculinity research and on the other hand the more established women’s- and gender studies. The field is described with references to central theoretical and methodological positions within the humanities and social studies during the last decades. On this background, advantages and disadvantages of the current differentiation and the many different concepts are discussed ad well as the future perspectives of the field.